Analytical and numerical investigations of base isolation system with negative stiffness devices. (1st October 2022) - Chen, Peng; Wang, Bin; Dai, Kaoshan; Li, Tao
Highlights: A two-stage design concept of negative stiffness devices (NSDs) is implemented. Theoretical dynamic solutions of the isolation system with NSDs are derived and the limitations are also verified. The proposed NSDs can promote the isolation effect and protect the system from extreme earthquakes. Abstract: This study presents an innovative base isolation system with negative stiffness devices (NSDs) for seismic protection of structures. It is implemented by the vertical pre-stressed helical springs to generate variable stiffness in the lateral direction. The design concept of the NSDs is first introduced, and the induced lateral restoring force was given accordingly. The equation of motion with strong nonlinearity is established and simplified using the Taylor series expansion. The theoretical dynamic solution is obtained using the harmonic balance method, which is further compared with the numerical approach using the direct integration method. Results show that the theoretical solution could match well with numerical simulation when the system nonlinearity is insignificant. For this reason, a corresponding parameter with its recommended critical value is provided to determine the applicability of the analytical approach. Performance evaluation of the isolation system with NSDs is conducted through the incremental dynamic analysis using two single-degree-of-freedom models. As expected, the auxiliary NSDs promote the isolation effect under minor and moderate earthquakes, while the large isolation deformation could be reduced under major earthquakes. Moreover, the NSDs are especially effective under near-field earthquakes with pulse-like components. Some potential drawbacks of this isolation system are also discussed, including the potential amplified acceleration response induced by the restraining of excessive displacement and considerable residual deformation after earthquake shaking.